Carbon-coated porous high-entropy alloy nano array catalyst and preparation method thereof
By using carbon-coated porous high-entropy alloy nanoarray catalyst in seawater electrolysis, combining the advantages of high-entropy alloy, carbon materials and MXene, the problems of low activity, easy corrosion and poor stability in seawater environments are solved, and the problem of traditional catalysts is achieved. High-efficiency and low-cost electrolytic catalytic performance of seawater.
Patent Information
- Application Number
- CN202411497080.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional high-entropy alloys are susceptible to chloride ions in seawater electrolysis and insufficient exposure of active sites, resulting in poor electrocatalytic performance and poor stability, which limits its application in seawater electrolysis.
Using carbon-coated porous high-entropy alloy nanoarray catalyst, the porous structure is constructed by compositeing high-entropy alloy with carbon material and MXene, and using carbon cladding to protect the high-entropy alloy core. MXene provides high-conductive electron transmission channels and enhances the material. specific surface area and stability.
It significantly improves electrocatalytic activity and durability, reduces the side reaction of chlorine analysis, improves hydrogen purity and efficiency, provides a low-cost and efficient seawater electrolytic catalyst, and solves the low activity and corrosion of traditional catalysts in seawater environments. Poor stability problem.
Smart Images

Figure CN119265610A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a carbon-coated porous high-entropy alloy nano-array catalyst and a preparation method thereof. Background Art
[0002] Seawater electrolysis has attracted extensive attention in recent years as a clean and efficient way to produce hydrogen. Compared with traditional freshwater electrolysis, seawater electrolysis has the advantages of abundant resources and sustainability, and provides a new way to solve energy crises and environmental problems. However, seawater electrolysis faces many challenges, the most important of which are the corrosion of electrode materials by impurity ions (such as chloride ions, magnesium ions, etc.) in seawater and the side reaction of chlorine evolution. These factors seriously affect the electrolysis efficiency and the stability of the electrode.
[0003] As a new type of material, high-entropy alloy (HEA) has shown broad application prospects in catalysis, energy and other fields due to its unique composition and structure. Especially in the field of electrocatalysis, the composition adjustability, structural stability and abundant active sites of HEA make it a hot research topic. However, traditional HEA materials still face some challenges in harsh environments such as seawater electrolysis, such as insufficient exposure of active sites, poor stability and susceptibility to chloride ion corrosion.
[0004] In order to overcome the above problems, researchers have tried to improve the electrocatalytic performance of HEA through nano-sizing and structural regulation. For example, preparing HEA into nanoparticles can increase the specific surface area and expose more active sites. However, most existing studies focus on the preparation of nanoparticles, and there are relatively few studies on HEA nanomaterials with clear morphology and porous structure. In addition, during the electrolysis of seawater, the corrosion of electrode materials by chloride ions is a serious problem, which limits the application of HEA in seawater electrolysis. Summary of the invention
[0005] The purpose of the present invention is to provide a highly catalytically active carbon-coated porous high-entropy alloy nanoarray catalyst for seawater electrolysis hydrogen production and a preparation method thereof, in order to solve one or more technical problems existing in the prior art and to provide at least a beneficial solution or option.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions.
[0007] A method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst, the preparation steps of which are as follows: 1) adding reagent A to a solvent, uniformly dispersing it by ultrasonication, then dissolving a metal salt and urea in deionized water and adding them to solution A, reacting them by magnetic stirring under oil bath conditions in a protective atmosphere to obtain reactant 1; 2) dissolving reagent B in deionized water, adding an acid solution to adjust the pH value, adding reactant 1 thereto, and ultrasonically treating it, then adding reagent C to the above suspension to react, to obtain reactant 2; 3) placing reactant 2 in a tubular furnace in a protective atmosphere for heat treatment, to obtain a carbon-coated porous high-entropy alloy nanoarray catalyst.
[0008] Wherein, the reagent A is selected from one of Ti3C2-MXene, Ti2C-MXene, V4C3-MXene, V2C-MXene, Mo2C-MXene, Ta4C3-MXene, Ta2C-MXene, Nb4C3-MXene, Nb2C-MXene, Zr2C-MXene, Ti2N-MXene, Ti4N3-MXene, TiVC-MXene, VCrC-MXene, TiNbC, VNbC-MXene, Ti2VC2-MXene, Cr2TiC2-MXene, Mo2Ti2C3-MXene, Mo2TiC2-MXene, Mo2Ga2C-MXene, and TiVCrMoC3-MXene.
[0009] The reagent B is a buffer used to maintain the pH value of the solution stable; the reagent B is one or more of ethanolamine, triethanolamine, N,N-dimethylformamide, N,N-dihydroxymethylethylamine, trishydroxymethylaminomethane, imidazole, and N-methylimidazole.
[0010] The reagent C is used to adjust the pH value; when the reagent B is dissolved in water, it forms a weak alkaline solution, and the reagent C neutralizes part of the reagent B by providing hydrogen ions, thereby adjusting the pH value to the target value; the reagent C is one of cyanamide, melamine, 1-(3,4-dihydroxyphenyl)-2-aminoethanol, phenethylamine, 4-hydroxyphenethylamine, 5-hydroxytryptamine, dopamine, and dopamine hydrochloride.
[0011] More preferably, the solvent is one or more of methanol, ethanol, ethylene glycol, isopropanol, ether, acetone, oleylamine, N,N-dimethylformamide, N-methylpyrrolidone, ethyl acetate, L-ascorbic acid solution, 2,5-dihydroxyterephthalic acid solution, hexadecyltrimethylammonium chloride solution, dichloromethane, benzene, toluene, petroleum ether, n-hexane, cyclohexane, oleic acid, formaldehyde and chloroform.
[0012] More preferably, the metal salt is selected from ferric sulfate, ferric nitrate, ferric acetate, ferric oxalate, ferric perchlorate, ferric chloride, ferrous chloride, ferric acetylacetonate, cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt oxalate, cobalt perchlorate, cobalt chloride, cobalt acetylacetonate, cobaltous acetylacetonate, nickel sulfate, nickel nitrate, nickel acetate, nickel oxalate, nickel perchlorate, nickel chloride, nickel acetylacetonate, copper sulfate, copper nitrate, copper acetate, copper oxalate, copper perchlorate, copper chloride, copper acetylacetonate, zinc sulfate, zinc nitrate, zinc acetate, zinc oxalate, zinc perchlorate, zinc chloride, manganese sulfate, manganese nitrate, manganese acetate, manganese oxalate, manganese perchlorate, manganese chloride, aluminum sulfate, aluminum nitrate, aluminum acetate, aluminum oxalate, aluminum perchlorate, aluminum chloride , chromium chloride, chromium sulfate, chromium acetate, chromium nitrate, chromium hexacarbonyl, cadmium sulfate, cadmium nitrate, cadmium acetate, cadmium oxalate, cadmium perchlorate, cadmium chloride, molybdenum chloride, sodium molybdate, molybdenum hexacarbonyl, tungsten chloride, ammonium tungstate, sodium tungstate, tungsten hexacarbonyl, palladium sulfate, palladium nitrate, palladium acetate, palladium chloride, di(acetylacetonate)palladium, potassium chloropalladate, platinum nitrate, chloroplatinic acid, platinum acetate, platinum acetylacetonate, potassium chloroplatinite, ruthenium chloride, ammonium hexachlororuthenate, triruthenium dodecacarbonyl, ruthenium acetylacetonate, gold chloride, chloroauric acid, iridium chloride, chloroiridic acid, ammonium chloroiridate, rhodium chloride, rhodium nitrate, rhodium sulfate, rhodium triacetylacetonate (III), rhodium dicarbonyl acetylacetonate, silver nitrate, silver acetate, yttrium (III) acetate hydrate, yttrium(III) acetate tetrahydrate, yttrium(III) nitrate hydrate, yttrium(III) sulfate octahydrate, uranium nitrate, samarium nitrate, vanadium chloride, ammonium metavanadate, vanadium hexacarbonyl, lanthanum nitrate, gadolinium nitrate, erbium nitrate, and ytterbium nitrate.
[0013] More preferably, the acid solution is selected from one of hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, hypochlorous acid, phosphoric acid, acetic acid, citric acid, hydrofluoric acid, formic acid, and oxalic acid.
[0014] More preferably, in step 1), the reaction temperature under the oil bath conditions is 40-200° C., and the reaction time is 2-48 hours.
[0015] More preferably, the protective atmosphere is selected from one of nitrogen, hydrogen, argon or a hydrogen / argon mixture.
[0016] More preferably, in step 2), the pH value ranges from 6 to 12.
[0017] More preferably, in step 2), the reaction time is 2 to 48 hours.
[0018] More preferably, in step 3), the temperature of the heating treatment is 100-1000° C., the heating rate is 1-15° C. / min, and the holding time of the heating treatment is 0.5-10 hours.
[0019] On the other hand, the present invention also provides a carbon-coated porous high-entropy alloy nanoarray catalyst prepared by the preparation method as described above.
[0020] The present invention adopts the above technical solution to have at least the following beneficial effects.
[0021] 1. The present invention proposes a new type of carbon-coated porous high-entropy alloy nanoarray catalyst, which combines the advantages of high-entropy alloy, carbon material and MXene. The multi-component composition of the high-entropy alloy gives it a rich electronic structure, which can adapt to different reaction intermediates, thereby reducing the reaction energy barrier. The carbon coating protects the high-entropy alloy core to prevent it from being corroded in the harsh seawater electrolysis environment. The high conductivity of MXene as a conductive substrate provides a fast channel for electron transmission for the reaction. This unique multi-dimensional structural design maximizes the advantages of each material. The synergistic effect between high-entropy alloy, carbon material and MXene significantly enhances the electrocatalytic activity of the material. In addition, the porous structure and nano-array structure greatly increase the specific surface area of the material, exposing more active sites, thereby increasing the reaction rate.
[0022] Second, by optimizing the composition and structure of high entropy alloys, the present invention is expected to inhibit the common chlorine evolution side reaction in the seawater electrolysis process, improve the purity and efficiency of hydrogen evolution, and provide a new way to prepare high-purity hydrogen. The present invention is expected to promote the development of seawater electrolysis technology, accelerate the use of clean energy, and provide new solutions to solve energy crises and environmental problems.
[0023] 3. The carbon-coated porous high-entropy alloy nanoarray catalyst prepared by the present invention exhibits excellent catalytic performance in the field of hydrogen production by electrolysis of seawater. Compared with traditional seawater electrolysis catalysts, the catalyst not only has higher catalytic activity, but also has lower cost and is easier to mass produce. Through the synergistic effect between high-entropy alloys, carbon materials and MXene, the catalyst effectively solves the problems of low activity, easy corrosion and poor stability of traditional catalysts in seawater environments. In addition, the present invention cleverly avoids the high-temperature sintering process, thereby preventing the collapse and agglomeration of the material, and significantly improves the specific surface area and the number of active sites of the material. As a conductive substrate, MXene not only provides a fast electron transmission channel for the reaction, but also enhances the stability of the material. This unique structural design and preparation process enable the catalyst of the present invention to exhibit excellent durability and corrosion resistance in hydrogen production by electrolysis of seawater, providing a new idea for the development of efficient and low-cost seawater electrolysis hydrogen production catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0025] Figure 1 Shown is a scanning electron microscope image of reagent A, i.e., Ti3C2-MXene, used in Example 1 of the present invention.
[0026] Figure 2 Shown is a scanning electron microscope image of reactant 1, namely FeCoNiCuRu-LDH / Ti3C2-MXene, prepared in Example 1 of the present invention.
[0027] Figure 3 Shown is a scanning electron microscope image of FeCoNiCuRu@C / Ti3C2-MXene prepared in Example 1 of the present invention.
[0028] Figure 4 Shown is a transmission electron microscope image of FeCoNiCuRu@C / Ti3C2-MXene prepared in Example 1 of the present invention. From the image, it can be seen that there is a carbon coating layer on the surface of the high entropy alloy FeCoNiCuRu.
[0029] Figure 5 Shown is the XRD pattern of FeCoNiCuRu@C / Ti3C2-MXene prepared in Example 1 of the present invention, from which it can be seen that a carbon peak exists.
[0030] Figure 6 Shown is the linear sweep voltammogram of the hydrogen evolution reaction of FeCoNiCuRu@C / Ti3C2-MXene and Ni@ / Ti3C2-MXene prepared in Example 1 of the present invention in seawater.
[0031] Figure 7 Shown is a scanning electron microscope image of FeCoNiCuMnZn@C / Ti3C2-MXene prepared in Example 2 of the present invention.
[0032] Figure 8 Shown is a scanning electron microscope image of CoNiCuMnAl@C / Ti2C-MXene prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the essence of the present invention, the specific implementation methods of the present invention are described in detail below with reference to the accompanying drawings.
[0034] The present invention provides a method for preparing a carbon-coated porous high-entropy alloy nanoarray, which can overcome the problems of easy corrosion and poor stability of catalysts prepared by the prior art.
[0035] The present invention provides a novel carbon-coated porous high-entropy alloy nanoarray. By compounding the high-entropy alloy with carbon materials and MXene and constructing a porous structure, the conductivity, specific surface area and stability of the material can be effectively improved. At the same time, the carbon coating layer can protect the high-entropy alloy core and prevent it from being corroded by chloride ions in a seawater environment. The high conductivity of MXene provides a fast channel for electron transmission for the reaction. This unique structural design can not only expose more active sites, but also improve the corrosion resistance of the material, thereby significantly improving its catalytic performance in seawater electrolysis.
[0036] The raw materials used in the following examples without explanation of the preparation methods are all commercially available. Example 1.
[0037] This embodiment provides a first carbon-coated porous high-entropy alloy nanoarray catalyst, and the preparation method thereof is as follows.
[0038] 1) Ti3C2-MXene was added to N-methylpyrrolidone and ultrasonically dispersed uniformly, and then iron nitrate, cobalt nitrate, nickel nitrate, copper nitrate, ruthenium chloride and urea were dissolved in deionized water and added thereto. Under nitrogen protection gas, the reaction was carried out in an oil bath at 100°C with magnetic stirring for 5 hours, and then washed, filtered and freeze-dried in sequence to obtain reactant 1. The scanning electron micrographs of Ti3C2-MXene and reactant 1 are shown in FIG. Figure 1 , Figure 2 shown.
[0039] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0040] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is raised from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a Ti3C2-MXene-supported carbon-coated porous iron-cobalt-nickel-copper-ruthenium nanoarray catalyst (FeCoNiCuRu@C / Ti3C2-MXene).
[0041] The electron microscope image of the Ti3C2-MXene-supported carbon-coated porous iron-cobalt-nickel-copper-ruthenium nanoarray catalyst (FeCoNiCuRu@C / Ti3C2-MXene) prepared in this example is as follows: Figure 3 As shown, from Figure 3It can be seen that the Ti3C2-MXene-supported carbon-coated porous iron-cobalt-nickel-copper-ruthenium nanoarray catalyst (FeCoNiCuRu@C / Ti3C2-MXene) has an orderly arranged structure composed of nanoscale material units, that is, it has a nanoarray structure.
[0042] from Figure 4 , Figure 5 It can be seen that the Ti3C2-MXene-supported carbon-coated porous iron-cobalt-nickel-copper-ruthenium nanoarray catalyst (FeCoNiCuRu@C / Ti3C2-MXene) prepared in this embodiment has a carbon peak and a carbon coating layer on the surface of the high entropy alloy FeCoNiCuRu.
[0043] from Figure 6 It can be seen that the Ti3C2-MXene-loaded carbon-coated porous iron-cobalt-nickel-copper-ruthenium nanoarray catalyst (FeCoNiCuRu@C / Ti3C2-MXene) prepared in this embodiment has improved catalytic activity, and is expected to better inhibit the common chlorine evolution side reaction in the seawater electrolysis process and improve the purity and efficiency of hydrogen evolution. Example 2.
[0044] This embodiment provides a second carbon-coated porous high-entropy alloy nanoarray catalyst, and its preparation method is as follows.
[0045] 1) Ti3C2-MXene was added to N,N-dimethylformamide and ultrasonically dispersed uniformly. Subsequently, iron nitrate, cobalt nitrate, nickel nitrate, copper nitrate, manganese nitrate, zinc nitrate and urea were dissolved in deionized water and added thereto. Under argon protective gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours. The mixture was then washed, filtered and freeze-dried in sequence to obtain reactant 1.
[0046] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0047] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is raised from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a Ti3C2-MXene-supported carbon-coated porous iron-cobalt-nickel-copper-manganese-zinc nanoarray catalyst (FeCoNiCuMnZn@C / Ti3C2-MXene).
[0048] The FeCoNiCuMnZn@C / Ti3C2-MXene prepared in this example also has a nanoarray structure, and its scanning electron microscope image at 2 μm is as follows: Figure 7 shown. Example 3.
[0049] This embodiment provides a third carbon-coated porous high-entropy alloy nanoarray catalyst, and its preparation method is as follows.
[0050] 1) Ti2C-MXene was added to N-methylpyrrolidone and ultrasonically dispersed uniformly. Subsequently, cobalt acetate, nickel acetate, copper acetate, manganese acetate, aluminum nitrate and urea were dissolved in deionized water and added thereto. Under nitrogen protective gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours. The mixture was then washed, filtered and freeze-dried in sequence to obtain reactant 1.
[0051] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0052] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is increased from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a Ti2C-MXene-supported carbon-coated porous cobalt nickel copper manganese aluminum nanoarray catalyst (CoNiCuMnAl@C / Ti2C-MXene).
[0053] The CoNiCuMnAl@C / Ti2C-MXene prepared in this example also has a nanoarray structure, and its scanning electron microscope image at 1 μm is as follows: Figure 7 shown. Example 4.
[0054] This embodiment provides a fourth carbon-coated porous high-entropy alloy nanoarray catalyst, and its preparation method is as follows.
[0055] 1) V2C-MXene was added to N-methylpyrrolidone and ultrasonically dispersed uniformly. Subsequently, ferrous sulfate, cobalt sulfate, nickel sulfate, rhodium sulfate, chloroplatinic acid and urea were dissolved in deionized water and added thereto. Under argon protective gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours. The mixture was then washed, filtered and freeze-dried in sequence to obtain reactant 1.
[0056] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0057] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is increased from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a V2C-MXene-supported carbon-coated porous iron-cobalt-nickel-platinum-rhodium nanoarray catalyst (FeCoNiPtRh@C / V2C-MXene).
[0058] Scanning electron microscopy showed that the FeCoNiPtRh@C / V2C-MXene prepared in this example had a nanoarray structure. Example 5.
[0059] This embodiment provides a fifth carbon-coated porous high-entropy alloy nanoarray catalyst, and its preparation method is as follows.
[0060] 1) Mo2C-MXene was added to N-methylpyrrolidone and ultrasonically dispersed uniformly, and then cobalt nitrate, nickel nitrate, iron nitrate, chromium nitrate, copper nitrate and urea were dissolved in deionized water and added thereto. Under nitrogen protection gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours, and then washed, filtered and freeze-dried in sequence to obtain reactant 1.
[0061] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0062] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is raised from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a Mo2C-MXene-supported carbon-coated porous iron-cobalt-nickel-copper-chromium nanoarray catalyst (FeCoNiCuCr@C / Mo2C-MXene).
[0063] Scanning electron microscopy observation showed that the FeCoNiCuCr@C / Mo2C-MXene prepared in this example had a nanoarray structure. Example 6.
[0064] This embodiment provides a sixth carbon-coated porous high-entropy alloy nanoarray catalyst, and its preparation method is as follows.
[0065] 1) Ta4C3-MXene was added to N-methylpyrrolidone and ultrasonically dispersed uniformly. Subsequently, cobalt acetylacetonate, nickel acetylacetonate, platinum acetylacetonate, ruthenium acetylacetonate, and iridium acetylacetonate were dissolved in ethanol and urea was dissolved in deionized water and then added thereto. Under nitrogen protection gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours. The mixture was then washed, filtered, and freeze-dried in sequence to obtain reactant 1.
[0066] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0067] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is raised from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a Ta4C3-MXene-supported carbon-coated porous cobalt nickel platinum ruthenium iridium nanoarray catalyst (CoNiPtRuIr@C / Ta4C3-MXene).
[0068] Scanning electron microscopy observation showed that the CoNiPtRuIr@C / Ta4C3-MXene prepared in this example had a nanoarray structure. Example 7.
[0069] This embodiment provides a seventh carbon-coated porous high-entropy alloy nanoarray catalyst, and its preparation method is as follows.
[0070] 1) Mo2Ti2C3-MXene was added to N-methylpyrrolidone and ultrasonically dispersed uniformly. Subsequently, ferrous acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, chloroplatinic acid, chloropalladic acid and urea were dissolved in deionized water and added thereto. Under argon protective gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours. The mixture was then washed, filtered and freeze-dried in sequence to obtain reactant 1.
[0071] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0072] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is increased from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a Mo2Ti2C3-MXene-supported carbon-coated porous iron-cobalt-nickel-platinum-palladium nanoarray catalyst (FeCoNiPtPd@C / Mo2Ti2C3-MXene).
[0073] Scanning electron microscopy showed that the FeCoNiPtPd@C / Mo2Ti2C3-MXene prepared in this example had a nanoarray structure. Example 8.
[0074] This embodiment provides an eighth carbon-coated porous high-entropy alloy nanoarray catalyst, and its preparation method is as follows.
[0075] 1) Mo2TiC2-MXene was added to N,N-dimethylformamide and ultrasonically dispersed uniformly. Subsequently, ferric chloride, nickel chloride, cupric chloride, chloroplatinic acid, rhodium chloride and urea were dissolved in deionized water and added thereto. Under nitrogen protective gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours. The mixture was then washed, filtered and freeze-dried in sequence to obtain reactant 1.
[0076] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0077] 3) The reactant 2 obtained in step 2) is placed in a tubular furnace for high-temperature heat treatment, and the temperature is raised from room temperature to 600°C at a heating rate of 3°C per minute in a hydrogen / argon mixture, and reacted at this temperature for 6 hours to obtain a Mo2TiC2-MXene-supported carbon-coated porous iron-nickel-copper-platinum-rhodium nanoarray catalyst (FeNiCuPtRh@C / Mo2TiC2-MXene).
[0078] Scanning electron microscopy observation showed that the FeNiCuPtRh@C / Mo2TiC2-MXene prepared in this example had a nanoarray structure.
[0079] Comparative example 1.
[0080] This embodiment provides a comparative example, and its preparation method is as follows.
[0081] 1) Ti3C2-MXene was added to N-methylpyrrolidone and ultrasonically dispersed uniformly, and then iron nitrate, cobalt nitrate, nickel nitrate, copper nitrate, ruthenium chloride and urea were dissolved in deionized water and added thereto. Under nitrogen protection gas, the mixture was reacted with magnetic stirring at 100°C in an oil bath for 5 hours, and then washed, filtered and freeze-dried in sequence to obtain reactant 1.
[0082] 2) Dissolve tris(hydroxymethyl)aminomethane in deionized water, and add hydrochloric acid solution to adjust the pH to 8.5, add the reactant 1 obtained in the above step 1) thereto, and perform ultrasonic treatment, then add the reagent dopamine hydrochloride to the above suspension and react with magnetic stirring for 12 hours, centrifuge the obtained product, wash with anhydrous ethanol and then dry to obtain reactant 2.
[0083] 3) The reactant 2 obtained in step 2) is placed in a tube furnace for high-temperature heat treatment. In an oxygen protective gas, the temperature is raised from room temperature to 600° C. at a rate of 3° C. per minute, and the reaction is carried out at this temperature for 6 hours.
[0084] The comparative example method cannot be used to obtain the Ti3C2-MXene-loaded porous high-entropy alloy nanoarray catalyst.
[0085] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0086] The above embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. The parts not described in the specific embodiments are all prior art or common knowledge.
[0087] It should be noted that, in the description of the present invention, the content of the present invention can be more easily understood by referring to the detailed description of the preferred implementation method of the present invention and the embodiments included. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail.
[0088] In the present invention, the term "prepared from..." is used synonymously with "comprising". The terms "comprising", "including", "having", "containing" or any other variation thereof, as used in the present invention, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0089] In the present invention, when an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in the present invention, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0090] In addition, the indefinite articles "a" and "an" before the elements or components of the present invention have no restrictions on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number is obviously intended to be in the singular form.
Claims
1. A method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst, characterized in that: The preparation steps are as follows: 1) Add reagent A to the solvent and disperse it evenly by ultrasonication. Then, dissolve the metal salt and urea in deionized water and add them to solution A. In a protective atmosphere, stir the mixture under magnetic stirring under oil bath conditions to obtain reactant 1. 2) Reagent B is dissolved in deionized water, and an acid solution is added to adjust the pH value, reactant 1 is added thereto, and ultrasonic treatment is performed, and then reagent C is added to the above suspension to react to obtain reactant 2; 3) In a protective atmosphere, the reactant 2 is placed in a tube furnace for heat treatment to obtain a carbon-coated porous high-entropy alloy nanoarray catalyst; The reagent A is selected from Ti3C2-MXene, Ti2C-MXene, V4C3-MXene, V2C-MXene, Mo2C-MXene, Ta4C3-MXene, Ta2C-MXene, Nb4C3-MXene, Nb2C-MXene, Zr2C-MXene, Ti2N-MXene, Ti4N3 -One of MXene, TiVC-MXene, VCrC-MXene, TiNbC, VNbC-MXene, Ti2VC2-MXene, Cr2TiC2-MXene, Mo2Ti2C3-MXene, Mo2TiC2-MXene, Mo2Ga2C-MXene, and TiVCrMoC3-MXene; The reagent B is a buffer used to maintain the pH value of the solution stable; the reagent B is one or more of ethanolamine, triethanolamine, N,N-dimethylformamide, N,N-dihydroxymethylethylamine, trishydroxymethylaminomethane, imidazole, and N-methylimidazole; The reagent C is used to adjust the pH value; when the reagent B is dissolved in water, it forms a weakly alkaline solution, and the reagent C neutralizes part of the reagent B by providing hydrogen ions, thereby adjusting the pH value to the target value; The reagent C is one of cyanamide, melamine, 1-(3,4-dihydroxyphenyl)-2-aminoethanol, phenethylamine, 4-hydroxyphenethylamine, 5-hydroxytryptamine, dopamine, and dopamine hydrochloride.
2. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: The solvent is one or more of methanol, ethanol, ethylene glycol, isopropanol, ether, acetone, oleylamine, N,N-dimethylformamide, N-methylpyrrolidone, ethyl acetate, L-ascorbic acid solution, 2,5-dihydroxyterephthalic acid solution, hexadecyltrimethylammonium chloride solution, dichloromethane, benzene, toluene, petroleum ether, n-hexane, cyclohexane, oleic acid, formaldehyde and chloroform.
3. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: The metal salt is selected from ferric sulfate, ferric nitrate, ferric acetate, ferric oxalate, ferric perchlorate, ferric chloride, ferrous chloride, ferric acetylacetonate, cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt oxalate, cobalt perchlorate, cobalt chloride, cobalt acetylacetonate, cobaltous acetylacetonate, nickel sulfate, nickel nitrate, nickel acetate, nickel oxalate, nickel perchlorate, nickel chloride, nickel acetylacetonate, copper sulfate, copper nitrate, copper acetate, copper oxalate, copper perchlorate, copper chloride, copper acetylacetonate, zinc sulfate, zinc nitrate, zinc acetate, zinc oxalate, zinc perchlorate, zinc chloride, manganese sulfate, manganese nitrate, manganese acetate, manganese oxalate, manganese perchlorate, manganese chloride, aluminum sulfate, aluminum nitrate, aluminum acetate, aluminum oxalate, aluminum perchlorate, aluminum chloride, chromium chloride , chromium sulfate, chromium acetate, chromium nitrate, chromium hexacarbonyl, cadmium sulfate, cadmium nitrate, cadmium acetate, cadmium oxalate, cadmium perchlorate, cadmium chloride, molybdenum chloride, sodium molybdate, molybdenum hexacarbonyl, tungsten chloride, ammonium tungstate, sodium tungstate, tungsten hexacarbonyl, palladium sulfate, palladium nitrate, palladium acetate, palladium chloride, di(acetylacetonate)palladium, potassium chloropalladate, platinum nitrate, chloroplatinic acid, platinum acetate, platinum acetylacetonate, potassium chloroplatinite, ruthenium chloride, ammonium hexachlororuthenate, triruthenium dodecacarbonyl, ruthenium acetylacetonate, gold chloride, chloroauric acid, iridium chloride, chloroiridic acid, ammonium chloroiridate, rhodium chloride, rhodium nitrate, rhodium sulfate, rhodium triacetylacetonate (III), rhodium dicarbonyl acetylacetonate, silver nitrate, silver acetate, yttrium (III) acetate hydrate, yttrium(III) acetate tetrahydrate, yttrium(III) nitrate hydrate, yttrium(III) sulfate octahydrate, uranium nitrate, samarium nitrate, vanadium chloride, ammonium metavanadate, vanadium hexacarbonyl, lanthanum nitrate, gadolinium nitrate, erbium nitrate, and ytterbium nitrate.
4. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: The acid solution is selected from one of hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, hypochlorous acid, phosphoric acid, acetic acid, citric acid, hydrofluoric acid, formic acid, and oxalic acid.
5. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: In step 1), the reaction temperature under the oil bath condition is 40-200° C., and the reaction time is 2-48 hours.
6. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: The protective atmosphere is selected from one of nitrogen, hydrogen, argon or a hydrogen / argon mixed gas.
7. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: In step 2), the pH value ranges from 6 to 12.
8. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: In step 2), the reaction time is 2 to 48 hours.
9. The method for preparing a carbon-coated porous high-entropy alloy nanoarray catalyst according to claim 1, characterized in that: In step 3), the temperature of the heating treatment is 100-1000° C., the heating rate is 1-15° C. / min, and the holding time of the heating treatment is 0.5-10 hours.
10. A carbon-coated porous high-entropy alloy nanoarray catalyst prepared by the preparation method according to any one of claims 1 to 9.